Tasawuf Urban dan Tasawuf Perenial dalam Kehidupan Masyarakat Perkotaan - Diah Arvionita; Efendi Efendi; Eka Putra Wirman; Zainal Zainal (Jurnal Pemikiran Islam, 2023)
Sufism is a concept within Islam that aims to lead individuals towards God. The practice of Sufism involves purifying the inner self through righteous deeds. In the journey of Sufism, there are three stages to be traversed: knowledge as the beginning, action as the middle, and God's grace as the culmination. By practicing Sufism, individuals can attain a deeper relationship with God and find inner peace. Through the process of purifying the inner self and engaging in righteous deeds, Sufism helps individuals enhance their spiritual quality and gain a profound understanding of their religion. In the contemporary era, Sufism has experienced development, marked by the emergence of new terms such as Urban Sufism and Perennial Sufism. Urban Sufism refers to the practice of Sufism in urban contexts, where individuals apply Sufi principles in their daily lives amidst the modern and complex urban environment. This demonstrates the adaptation of Sufism to the challenges and needs of the present time. On the other hand, Perennial Sufism refers to an approach that connects the essence of mystical and spiritual teachings from various religions. In Perennial Sufism, the common principles of spirituality and religious experiences are found across different religious traditions, serving as a bridge to understand and achieve unity with God.AbstrakTasawuf sebuah konsep dalam Islam yang memiliki tujuan untuk membawa manusia menuju Tuhan. Praktik tasawuf melibatkan pensucian batin dengan amal shaleh. Dalam perjalanan tasawuf, terdapat tiga tahapan yang harus dilalui, yaitu ilmu sebagai yang awal, amal sebagai yang tengah, dan karunia Allah sebagai yang akhir. Dengan mengamalkan tasawuf, individu dapat mencapai hubungan yang lebih mendalam dengan Tuhan dan memperoleh kedamaian dalam jiwa. Melalui proses pensucian batin dan pelaksanaan amal shaleh, tasawuf membantu manusia untuk meningkatkan kualitas spiritualitasnya dan memperoleh pemahaman yang lebih mendalam tentang agama. Perkembangan tasawuf di era kontemporer saat ini, yang ditandai dengan munculnya beberapa istilah baru seperti Tasawuf Urban atau Tasawuf Perkotaan dan Tasawuf Perenial. Tasawuf Urban mengacu pada praktik tasawuf yang dilakukan dalam konteks perkotaan, di mana individu mengaplikasikan prinsip-prinsip tasawuf dalam kehidupan sehari-hari di tengah kehidupan perkotaan yang modern dan kompleks. Hal ini menunjukkan adaptasi tasawuf dengan tantangan dan kebutuhan zaman. Sementara itu, Tasawuf Perenial merujuk pada pendekatan tasawuf yang menghubungkan inti dari ajaran-ajaran mistis dan spiritual dari berbagai agama. Dalam Tasawuf Perenial, kesamaan prinsip-prinsip spiritual dan pengalaman keagamaan ditemukan di seluruh tradisi agama, dan hal ini digunakan sebagai jembatan untuk memahami dan mencapai kesatuan dengan Tuhan